Numerical simulation of microstructure of brittle rock using a grain-breakable distinct element grain-based model. (September 2016) - Gao, Fuqiang; Stead, Doug; Elmo, Davide
Abstract: A distinct element grain-based method (GBM) was developed to simulate the microstructure of rock-like materials. Using this method, a UDEC-GBM model can be readily constructed with a given mineral composition, allowing independent assignment of specific properties to both the grains and grain boundaries. Both intra-granular cracks cutting through the grains and inter-granular cracks developed along grain boundaries can be captured. These features allow a full incorporation of both geometric and mechanical heterogeneity at grain scale for simulating brittle rocks. The validity of the proposed UDEC-GBM approach was verified by simulating a low-porosity sandstone under compression and direct-shear tests. The UDEC-GBM was proved to be capable of reproducing many of the characteristics associated with brittle fracture in low-porosity sandstone. It was found that the model with unbreakable grains trends to under-estimate the crick initiation threshold, highlighting the importance of the incorporation of breakable grains when modeling micro-structure of brittle rocks. The numerical experiments suggested that examining the extent of the tensile stress zones alone may lead to a biased evaluation of tensile cracking at crack initiation. The tensile stress magnitude must also be taken into consideration. It was also found that a synthetic sandstone sample with relatively low ground boundary strength produces a more ductile post-peak behavior. Microscopic tensile strength of the grains has limited influence on the failure mechanism of the synthetic specimen under unconfined compression loading. The proposed GBM approach provides a very useful tool for studying grain-scale micro-mechanics of brittle rocks.